The Effect of the Establishment of a New Autonomous Region on Electoral District Regulations in the 2024 General Election - Danang Sa'adawisna; Bayu Karunia Putra (Peneliti.net, 2022)
This article aims to determine the arrangement of electoral districts formed to conduct competition in general elections (elections) that are proportional to the number of representatives contested in one area. This topic is important and interesting, because it relates to the arrangement of electoral districts within the DPR, there are differences with the arrangement of electoral districts within the Regency/City DPRD, where the scope of the DPR is in accordance with the regulations regulated by the government and DPR in Law Number 7 of 2017 concerning Elections. In general, as well as within the scope of the Regency/City DPRD, it can be adjusted to regional developments which have been further regulated in KPU RI Decree Number 18/PP.02-Kpt/03/KPU/I/2018 concerning Technical Instructions for Structuring Electoral Districts and Allocation of Representative Council seats. Regency/City Regional People in the General Election. The research method used is the literature review method, where sources and data are obtained through the Publish or Perish, SINTA, and Goggle Scholar databases. In this method, the researcher uses a descriptive qualitative approach, where this method utilizes qualitative data and is described descriptively. The data collection technique uses a literature review technique carried out by researchers to collect valid, complete, and relevant information related to the topic of the problem that is the object of research. The data analysis technique used a literature review analysis technique, where this research was carried out by reading library sources to obtain the necessary data. The author finds that, the addition of new provinces as a result of the division of Papua Province with New Autonomous Regions (DOB) such as South Papua Province, Central Papua, and Papua Mountains will cause changes to the number of seats and electoral districts of the DPR, where there are obstacles in its implementation. which is not in accordance with the regulations regarding general elections (elections), then this amendment is carried out to result in the 2024 general election (election) obtaining strong legitimacy from the people without violating the applicable provisions.